2011
DOI: 10.1088/2041-8205/727/2/l33
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a Thermal Spectral Component in the Prompt Emission of GRB 100724b

Abstract: Observations of GRB 100724B with the Fermi Gamma-Ray Burst Monitor find that the spectrum is dominated by the typical Band functional form, which is usually taken to represent a non-thermal emission component, but also includes a statistically highly significant thermal spectral contribution. The simultaneous observation of the thermal and non-thermal components allows us to confidently identify the two emission components. The fact that these seem to vary independently favors the idea that the thermal compone… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

36
276
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(313 citation statements)
references
References 28 publications
36
276
1
Order By: Relevance
“…However recent GRB studies with Fermi have suggested that there are a number of GRBs whose spectral behaviour differs from a Band function, with a number of different spectral components invoked in order to explain these observations (e.g. Asano et al 2009;Burgess et al 2011;Guiriec et al 2011;Pe'er et al 2012). The Fermi data cover a wide energy band with high spectral resolution and so the systematic study of low-energy spectral deviations in bright Fermi bursts presented here enables the frequency of such events to be investigated.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However recent GRB studies with Fermi have suggested that there are a number of GRBs whose spectral behaviour differs from a Band function, with a number of different spectral components invoked in order to explain these observations (e.g. Asano et al 2009;Burgess et al 2011;Guiriec et al 2011;Pe'er et al 2012). The Fermi data cover a wide energy band with high spectral resolution and so the systematic study of low-energy spectral deviations in bright Fermi bursts presented here enables the frequency of such events to be investigated.…”
Section: Discussionmentioning
confidence: 94%
“…The prompt emission of GRBs has been detected over a wide spectral range from keV to GeV energies and is generally well modelled by one or a combination of the following: a smoothly broken power-law (e.g. Band et al 1993;Abdo et al 2009b), a quasi-thermal component (e.g., Preece 2000; Guiriec et al 2011;Ryde et al 2011;Axelsson et al 2012), an extra nonthermal power-law component extending to high energies (e.g. González et al 2003;Kaneko et al 2008;Abdo et al 2009a) or a cut-off in the MeV regime (e.g., Ackermann et al 2012b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy spectrum is highly non-thermal and is usually described empirically by the Band function (Band et al 1993), a smoothly joined broken power-law whose νF ν spectrum peaks at E p of a few hundred keV (Preece et al 2000;Kaneko et al 2006;Guidorzi et al 2011;Goldstein et al 2012;Gruber et al 2014;Bošnjak et al 2014), in some cases accompanied by a mostly subdominant thermal component (e.g. Guiriec et al 2011Guiriec et al , 2015; see Pe'er 2015 for a review). An ultra-relativistic outflow (with Lorentz factor Γ of a few 10 2 ) is required to reduce the pair production Full Table 1 is only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/589/A97 opacity and explain why a non-thermal spectrum extending to the MeV and GeV ranges is observed (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Determinations of coefficients a and b of correlations could tell us whether these empirical luminosity correlations are independent on the redshift, which is very crucial for treating GRB as the distance indicator to investigate the evolution of our Universe. In addition, some new models for GRB have been proposed in resent years, such as the spectro-temporal multicomponent model (Guiriec et al 2011(Guiriec et al , 2013(Guiriec et al , 2015a(Guiriec et al ,b, 2016a. Interestingly, this model could result in a new time-resolved relation: the relation between the luminosity of the non-thermal component, L nTH i…”
Section: Introductionmentioning
confidence: 99%